The determinants of corporate board size and composition: An empirical analysis - Boone, Audra L.; Casares Field, Laura; Karpoff, Jonathan M.; Raheja, Charu G. (Journal of Financial Economics, 2007)
Using a unique panel dataset that tracks corporate board development from a firm's IPO through 10 years later, we find that: (i) board size and independence increase as firms grow and diversify over time; (ii) board size—but not board independence—reflects a tradeoff between the firm-specific benefits and costs of monitoring; and (iii) board independence is negatively related to the manager's influence and positively related to constraints on that influence. These results indicate that economic considerations—in particular, the specific nature of the firm's competitive environment and managerial team—help explain cross-sectional variation in corporate board size and composition. Nonetheless, much of the variation in board structures remains unexplained, suggesting that idiosyncratic factors affect many individual boards’ characteristics.